Synthetic jets as a flow control device for performance enhancement of vertical axis hydrokinetic turbines: A 3D computational study (2022)
In the present work, a vertical axis turbine with straight blades was analyzed through a numerical simulation in three dimensions, the performance of the turbine was studied while synthetic jets were used as an active flow control method. To carry out the simulations, the Unsteady Reynolds Averaged Navier-Stokes (URANS) equations were solved on Star CCMþ, through the k-ω SST turbulence model. The dynamics of the turbine movement were described using the Overset Mesh technique, capturing the transient characteristics of the flow field. Hydrodynamic coefficients and vorticity fields were obtained to describe the flow behaviour, and the results were compared with two-dimensional simulations of the same system. Turbine performance with tangential synthetic jets located on the intrados and extrados of the airfoil shows an increase in the torque and power output of the turbine. Moreover, using simple estimates, synthetic jets used less power than the increment in power generated at the turbine shaft, showing that efficiency of the turbine increases with the use of synthetic jets. However, the increment in the turbine performance is not as high as in previous two-dimensional studies reported in the literature